Wastewater Treatment and the Role of Laboratory Professionals. Issue 4 (9th September 2015) - Wagner, George H.
Abstract : Wastewater treatment combines biological, chemical, and physical unit processes to purify large volumes of sewage. Each unit process—often based on a naturally occurring process—targets specific contaminants in a unique way. By analyzing wastewater constituents at various stages of treatment, laboratory professionals play a vital role in the efficient operation of wastewater treatment plants and, thus, help to protect the environment and public health.